Antibiotic Susceptibility and Molecular Detection of Pseudomonas aeruginosa Isolated from Bovine Mastitis - AL-Taee, Hala S.R.; Al-Samarraae, Ikram A.A.; AL-Ahmed, Hazim I. (The Iraqi Journal of Veterinary Medicine, 2019)
This study aimed to isolate Pseudomonas aeruginosa from cattle (bovine) milk with mastitis to characterize its antimicrobial susceptibility against some antibiotics, and to identify aminoglycoside acetyltransferase (aac-3-Ib) gene.A total of 100 bovine milk samples were collected randomly from different local cow farms at districts of Wasit governorate, Iraq. Six P. aeruginosa isolates were obtained using bacterial culture method and further identified by Analytical Profile Index (API-20E). The antibiotic sensitivity test was performed by disc diffusion methods. Among the 5 antibiotics used, the highest resistance (100%) was found with Nalidixic acid andtetracycline, follow by gentamicin (50%) and the lowest resistance rate (16.6%, and 33.3%) was to the ciprofloxacin and cephalothin respectively. PCR was performed for all the gentamicin resistant isolates that be among the aminoglycoside family. The where the frequency of aac(3)-Ib gene have product (530bp) was to 3 of P. aeruginosa isolates. From the finding of present study we concluded that P.aeruginosa thatisolated from mastitic bovinehave been developed resistance against aminoglycosides through presence of aac(3)-Ibgene and the ciprofloxacin and cephalothin can be taken as good choice of treatment